2015
DOI: 10.1111/1750-3841.12926
|View full text |Cite
|
Sign up to set email alerts
|

The Elimination of Listeria Monocytogenes Attached to Stainless Steel or Aluminum Using Multiple Hurdles

Abstract: The results of this study will provide a better understanding and potential methods for the sanitization of industrial deli meat slicers. In turn, the knowledge gained from this study can reduce the risk of contamination and outbreaks of L. monocytogenes and other food-borne pathogens for consumers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…Many previous studies have evaluated combinations of heat treatment with sanitizers to eradicate or inhibit foodborne pathogens. Mertz et al [63] demonstrated that using quaternary ammonium compounds (5 or 10 ppm), chlorine (10 or 25 ppm), or peracetic acid alone resulted in a 2 to 3-log reduction in Listeria monocytogenes on stainless steel or aluminum surfaces, while moist heat alone led to a 3 to 4-log reduction. However, when moist heat and sanitizer were combined, there was a 5 to 7-log reduction compared to the initial inoculation.…”
Section: Effect Of Hot Water Pretreatment On the Efficacy Of Chlorine...mentioning
confidence: 99%
“…Many previous studies have evaluated combinations of heat treatment with sanitizers to eradicate or inhibit foodborne pathogens. Mertz et al [63] demonstrated that using quaternary ammonium compounds (5 or 10 ppm), chlorine (10 or 25 ppm), or peracetic acid alone resulted in a 2 to 3-log reduction in Listeria monocytogenes on stainless steel or aluminum surfaces, while moist heat alone led to a 3 to 4-log reduction. However, when moist heat and sanitizer were combined, there was a 5 to 7-log reduction compared to the initial inoculation.…”
Section: Effect Of Hot Water Pretreatment On the Efficacy Of Chlorine...mentioning
confidence: 99%